Perivascular localization of macrophages in the intestinal mucosa is regulated by Nr4a1 and the microbiome - Masaki Honda (Nature Portfolio, 2020)
Lamina propria macrophages are at the frontline of defense against intestinal pathogens. Here the authors reveal that CCR2 and NR4A1-dependent CX3CR1+ macrophages form a dense network around the vessels in the lamina propria, and implicate this anatomical structure into prevention of systemic bacterial dissemination.